Surgical margins in head and neck cancer: A contemporary review1. Issue 9 (3rd September 2012) - Hinni, Michael L.; Ferlito, Alfio; Brandwein‐Gensler, Margaret S.; Takes, Robert P.; Silver, Carl E.; Westra, William H.; Seethala, Raja R.; Rodrigo, Juan P.; Corry, June; Bradford, Carol R.; Hunt, Jennifer L.; Strojan, Primož; et al.
Abstract Adequate resection margins are critical to the treatment decisions and prognosis of patients with head and neck squamous cell carcinoma (HNSCC). However, there are numerous controversies regarding reporting and interpretation of the status of resection margins. Fundamental issues relating to the basic definition of margin adequacy, uniform reporting standards for margins, optimal method of specimen dissection, and the role of intraoperative frozen section evaluation, all require further clarification and standardization. Future horizons for margin surveillance offer the possible use of novel methods such as "molecular margins" and contact microscopic endoscopy, However, the limitations of these approaches need to be understood. The goal of this review was to evaluate these issues to define a more rational, standardized approach for achieving resection margin adequacy for patients with HNSCC undergoing curative resection. © 2012 Wiley Periodicals, Inc. Head Neck, 2013